The Value Realization Mechanism and Path Optimization of Art Integration into Contemporary Design——Based on Multi-Dimensional Empirical and Theoretical Verification - Liau, Khaixuan (International Journal of Multidisciplinary Research, 2026)
The in-depth integration of art and design is the core direction for the innovative development of the contemporary design industry. Their symbiosis can not only enrich the aesthetic level and innovative space of design works, but also promote the extension and upgrading of design value from the traditional functional level to the spiritual experience and social service levels. In the current practice of art and design integration, there are still many practical bottlenecks. Some designs fall into the misunderstanding of "formal grafting", simply applying artistic symbols but ignoring the in-depth integration of artistic connotation and design functions, resulting in the difficulty of converting artistic value into the core competitiveness of design. At the same time, some designs lack scientific artistic transformation paths and clear value orientation, which further reduces the quality and effectiveness of their integration. Taking "the value realization mechanism of art integration into contemporary design" as the core research topic, this paper, based on multiple perspectives such as design theory, visual culture theory and technology research, strictly relying on the designated references, comprehensively adopts the methods of literature research, case empirical research and comparative analysis to systematically define the value dimensions of art integration into contemporary design, deeply analyze the core links and key restrictive factors of value realization, construct a scientific and feasible value realization mechanism model, and put forward targeted path optimization strategies. It aims to solve the practical problem of "difficult value implementation" in the integration of art and design, improve the empirical research system in the field of art and design integration, and provide operable theoretical guidance and practical schemes for the coordinated unification of artistic value and design value in contemporary design practice. The research shows that the value of art integration into contemporary design is concentrated in three interrelated and symbiotic core dimensions: aesthetic value, innovative value and social value. Its value realization needs to follow the complete closed loop of "artistic element extraction - design transformation - value transmission - feedback optimization". The lack of design methods, insufficient technical adaptation and deviation in value orientation are the core crux that hinder the efficient operation of this closed loop and restrict the realization of value. The value realization mechanism model constructed in this paper, which combines the theoretical views of the designated references with empirical cases, makes up for the deficiency of existing research that focuses on "phenomenon description rather than mechanism construction" and "theoretical discussion rather than empirical verification" in the integration of art and design. It verifies the feasibility and scientificity of the mechanism through multi-field empirical cases, and improves the empirical research system in the field of art and design integration relying on the designated references, promoting the research in this field from the theoretical level to practical implementation and providing strong support for the high-quality development of contemporary design.